STUDY ON ZERO FLARE POLICY FOR OIL AND GAS EXPLORATION AND PRODUCTION INDUSTRY IN INDONESIA - R. Desrina; Supriyadi Supriyadi (Testing Center for Oil and Gas LEMIGAS, 2008)
Flaring is an essential practice in oil and gas production, primarily for safety reasons. Although data indicate that, on a worldwide basis, gas flaring contributes only 1% of anthropogenic carbon dioxide emissions, for environmental and resource conservation reasons, flaring should always be minimized as much as practicable. In the frame work of Global Gas Flaring Reduction Public-Private Partnership (GGFR), Government of Indonesia (GOI) through Directorate General of Oil and Gas is preparing a draft policy for Green Oil and Gas Industry Initiative (GOGII). GOI encourage oil and gas activity in Indonesia to be environmental friendly industries by implementing Zero Flare, Zero Discharge, Clean Air and Go Renewable programs. Zero flare can be achieved by different kind of methods, such as re-injection of associated gas, gas utilization on-site, and collection and market to downstream markets. This paper tries to review and evaluate the possibility of implementing the zero flare policy for oil and gas exploration and production industries in Indonesia, in the frame work of contributing to GOI in preparing draft policy for GOGII.